Letter of the King of Prussia Concerning the Education of Lithuanians in Prussia Written in 1807 in Klaipėda - Citavičiūtė, Liucija (Senoji Lietuvos literatūra, 2024)
The article shows how communication of King Frederick William III of Prussia with Prussian Lithuanians led to the drafting of a special decree (1807) on the state’s financial support for studies of Prussian Lithuanians. Written in Klaipėda, where the royal family was staying after Napoleon’s army had captured Berlin, the letter is addressed to Friedrich Leopold von Schröter, the chancellor of Prussia. This publication also presents sources that demonstrating that even at the end of the nineteenth century, when the German Reich had already been established, the decree was enforced, which implies that the Germanisation of Lithuanians in Lithuania Minor was not yet universal by the twentieth century. This is the first publication of the letter and its translation into Lithuanian.A German copy of the letter was published in the scientific journal Mitteilungen der Litauischen literarischen Gesellschaft, which was the first continuous publication on Lithuanian studies in German published in Tilžė between 1880 and 1912. The journal was produced by the Lithuanian Literary Society (Ger. Litauische literarische Gesellschaft), the first scientific centre for Lithuanian studies founded in Tilžė in 1879. The aim of the society was to study the history of Lithuania, the Lithuanian language, folklore, literature, and texts and to preserve and promote scientific and cultural monuments. Famous public figures, scientists, and writers of Lithuania Major and Lithuania Minor, such as Jonas Basanavičius, Vilius Gaigalaitis, Aleksandras Teodoras Kuršaitis, Jonas Šliūpas, Eduardas Volteris, and others collaborated with it.In the issue of 1894, Otto Julius Stein, a priest from Tilžė, published the collection of archival documents from the Napoleonic War Erinnerungen aus Litauen in Preußens Unglückszeit auf Grund kirchenurkundlichen Mitteilungen von Pfarrer Stein in Tilsit. The author gave exhaustive accounts or citations of the most significant documents, while the king’s letter was reproduced verbatim. The manuscript of this letter has not been found yet.
Keywords: Decree of Friedrich Wilhelm III; Napoleonic wars; Piktupėnai; education of Prussian Lithuanians; Germanisation